De novo synthesis of thiamine (vitamin B1) is the ancestral state in Plasmodium parasites – evidence from avian haemosporidians. Issue 8 (12th December 2017) - Hellgren, Olof; Bensch, Staffan; Videvall, Elin
Abstract: Parasites often have reduced genomes as their own genes become redundant when utilizing their host as a source of metabolites, thus losing their own de novo production of metabolites. Primate malaria parasites can synthesize vitamin B1 (thiamine) de novo but rodent malaria and other genome-sequenced apicomplexans cannot, as the three essential genes responsible for this pathway are absent in their genomes. The unique presence of functional thiamine synthesis genes in primate malaria parasites and their sequence similarities to bacterial orthologues, have led to speculations that this pathway was horizontally acquired from bacteria. Here we show that the genes essential for the de novo synthesis of thiamine are found also in avian Plasmodium species. Importantly, they are also present in species phylogenetically basal to all mammalian and avian Plasmodium parasites, i.e. Haemoproteus . Furthermore, we found that these genes are expressed during the blood stage of the avian malaria infection, indicating that this metabolic pathway is actively transcribed. We conclude that the ability to synthesize thiamine is widespread among haemosporidians, with a recent loss in the rodent malaria species.